Differential Tick Salivary Protein Profiles and Human Immune Responses to Lone Star Ticks (Amblyomma americanum) From the Wild vs. a Laboratory Colony - Maldonado-Ruiz, L. Paulina; Montenegro-Cadena, Lidia; Blattner, Brittany; Menghwar, Sapna; Zurek, Ludek; Londono-Renteria, Berlin (Frontiers in Immunology, 2019)
Ticks are a growing concern to human and animal health worldwide and they are leading vectors of arthropod-borne pathogens in the United States. Ticks are pool blood feeders that can attach to the host skin for days to weeks using their saliva to counteract the host defenses. Tick saliva, as in other hematophagous arthropods, contains pharmacological and immunological active compounds, which modulate local and systemic immune responses and induce antibody production. In the present study, we explore differences in the salivary gland extract (SGE) protein content of Amblyomma americanum ticks raised in a laboratory colony (CT) vs. those collected in the field (FT). First, we measured the IgG antibody levels against SGE in healthy volunteers residing in Kansas. ELISA test showed higher IgG antibody levels when using the SGE from CT as antigen. Interestingly, antibody levels against both, CT-SGE and FT-SGE, were high in the warm months (May–June) and decreased in the cold months (September–November). Immunoblot testing revealed a set of different immunogenic bands for each group of ticks and mass spectrometry data revealed differences in at 19 proteins specifically identified in the CT-SGE group and 20 from the FT-SGE group. Our results suggest that differences in the salivary proteins between CT-SGE and FT-SGE may explain the differential immune responses observed in this study.